Development of The Project Approach in Engineering Higher Education - V. V. Glushchenko (Universitas Pendidikan Indonesia (UPI), 2023)
The subject of this article is the methodological aspects of the development of project-based higher education at a machine-building university, the object of the article – higher education in mechanical engineering, the purpose of the article is to increase the efficiency of the processes of development of project higher education at the University of mechanical Engineering, to achieve this goal, the following tasks are solved: research of the essence of project education in mechanical engineering, clarification of the concept of